JOHN D. ROCKEFELLER, STANDARD OIL, AND THE RISE OF CORPORATE PUBLIC RELATIONS IN PROGRESSIVE AMERICA, 1902–1908. (23rd June 2017) - Leccese, Stephen R.
Abstract : When the Supreme Court ordered the dissolution of Standard Oil in 1911, it marked the end of an unsuccessful campaign by the company to improve its public standing. Standard Oil's failure to mollify public opinion in the aftermath of Ida Tarbell's muckraking masterpiece, "The History of the Standard Oil Company, " has resulted in a historiographical record that negatively assesses the company's response. This article reassesses the company response by placing it within the wider context of business history in the early twentieth century. It offers a detailed exploration of the public relations initiatives of Standard Oil from 1902 to 1908. Additionally, the article views the affair through the lens of standard corporate practices of the early Progressive Era, when large businesses had only begun to promote favorable public images. It argues that progressive reform inadvertently aided the rise of big business by teaching corporations the importance of promoting favorable public images. This wider context reveals that Standard Oil's public relations response, if unsuccessful, was not as aloof as others have argued. In fact, the company made a concerted effort to change public opinion about its business practices.